Money for Something: Braided Funding and the Structure and Output of Research Groups - Russell J. Funk; Britta Glennon; Julia Lane; Raviv Murciano-Goroff; Matthew B. Ross (Institute of Labor Economics (IZA), 2019)
In 2017, the federal government invested over 40 billion on university research; another 16 billion came from private sector sources. The expectation is that these investments will bear varied fruits, including outputs like more economic growth, more scientific advances, the training and development of future scientists, and a more diverse pipeline of STEM researchers; an expectation that is supported by the work of recent Nobel Laureate in Economics, Paul Romer. Yet volatility in federal funding, highlighted by a 35 day federal shutdown in early 2019, has resulted in an increased interest on the part of scientists in finding other sources of funding. Understanding the effect of such different funding streams on research outputs is thus of more than academic importance, particularly because there are likely to be tradeoffs, both in terms of the structure of research and in terms of research outputs. For example, federal funding is often intended to affect the structure of research, with explicit goals of training the next generation of scientists and promoting diversity; those goals are less salient for non-federal funding. On the output side, federally funded research may be more likely to emphasize producing purely scientific outputs, like publications, rather than commercial outputs, like patents. The contribution of this paper is to use new data to examine how different sources of financial support – which we refer to as "braided" funding – affect both the structure of scientific research and the subsequent outputs.
Keywords: O3; M5; H1; 330; UMETRICS; team science; research impact; science policy; research outputs